Diagnostics of Tin Plasma Produced by Visible and IR Nanosecond Laser Ablation. Issue 4 (4th December 2014) - Hanif, M.; Salik, M.
Abstract We present the optical emission spectroscopic studies of the Tin (Sn) plasma, produced by the fundamental (1064 nm) and second (532 nm) harmonics of a Q switched Nd: YAG pulsed laser having pulse duration of 5 ns and 10 Hz repetition rate which is capable of delivering 400 mJ at 1064 nm, and 200 mJ at 532 nm using Laser Induced Breakdown Spectroscopy (LIBS). The laser beam was focused on target material by placing it in air at atmospheric pressure. The experimentally observed line profiles of four neutral tin (Sn I) lines at 231.72, 248.34, 257.15 and 266.12 nm were used to extract the electron temperature (Te) using the Boltzmann plot method and determined its value 6360 and 5970 K respectively for fundamental and second harmonics of the laser. Whereas, the electron number density (Ne) has been determined from the Stark broadening profile of neutral tin (Sn I) line at 286.33 nm and determined its value 5.85 x 1016 and 6.80 x 1016cm–3 for fundamental and second harmonics of the laser respectively. Both plasma parameters (Te and Ne) have also been calculated by varying distance from the target surface along the line of propagation of plasma plume and also by varying the laser irradiance. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)